What's a parent to do? A review of four books about feeding children. Issue 2 (2nd July 2016) - Brown, Harriet
ABSTRACT: Books advising parents on how to get their children to lose weight and/or prevent weight gain have become ubiquitous, thanks to the escalating rhetoric about the "childhood obesity epidemic." This review looks at four books, each of which represents a common archetype of such books: Why Can't My Child Stop Eating? A Guide to Helping Your Child Overcome Emotional Overeating by Debbie Danowski; Ending the Food Fight: Guide Your Child to a Healthy Weight in a Fast Food/Fake Food World by David S. Ludwig; A Parent's Guide to Childhood Obesity: A Road Map to Health by the American Academy of Pediatrics; and Your Child's Weight: Helping Without Harming, Birth Through Adolescence by Ellyn Satter.